2008
DOI: 10.1007/s00424-008-0556-8
|View full text |Cite
|
Sign up to set email alerts
|

Genetic evidence for functional role of ryanodine receptor 1 in pulmonary artery smooth muscle cells

Abstract: Ryanodine receptor 1 (RyR1) is well-known to be expressed in systemic and pulmonary vascular smooth muscle cells (SMCs); however, its functional roles remain largely unknown. In the present study, we attempted to determine the potential importance of RyR1 in membrane depolarization-, neurotransmitter-, and hypoxia-induced Ca2+ release and contraction in pulmonary artery SMCs (PASMCs) using RyR1 homozygous and heterozygous gene deletion (RyR1−/− and RyR1+/−) mice. Our results indicate that spontaneous local Ca2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
38
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(43 citation statements)
references
References 30 publications
5
38
0
Order By: Relevance
“…Interestingly, membrane depolarization does not trigger normal Ca 2þ release from the SR in RyR2 À=þ airway SMCs (9). We have previously reported that both RyR1 and RyR3 gene deletion greatly inhibit the hypoxic increase in [Ca 2þ ] i in PASMCs (7,32). These results, together with the finding that hypoxia is all but incapable of inducing an increase in [Ca 2þ ] i in RyR2…”
Section: à=þsupporting
confidence: 64%
See 2 more Smart Citations
“…Interestingly, membrane depolarization does not trigger normal Ca 2þ release from the SR in RyR2 À=þ airway SMCs (9). We have previously reported that both RyR1 and RyR3 gene deletion greatly inhibit the hypoxic increase in [Ca 2þ ] i in PASMCs (7,32). These results, together with the finding that hypoxia is all but incapable of inducing an increase in [Ca 2þ ] i in RyR2…”
Section: à=þsupporting
confidence: 64%
“…This time period was chosen, because our previous studies have shown that maximal cellular responses occur before or at 5 min after acute hypoxic exposure (7,17,18,23,(30)(31)(32). In control experiments, tissues or cells were identically treated but exposed to a normoxic PSS.…”
Section: Hypoxiamentioning
confidence: 99%
See 1 more Smart Citation
“…The increase in RyR1 in HU animals could explain why the increase of CICR was induced by P2X1 activation (near 40 %). This result could be correlated with the spatial distribution and/or coupling of P2X1, VDCC and RyR subtypes in VSMC [10,11,23,43].…”
Section: Discussionmentioning
confidence: 72%
“…All animal experiments were approved by the Institutional Animal Care and Use Committee of Albany Medical College. PAs and PASMCs were prepared from Swiss-Webster mice (Taconic, Germantown, NY), as we described previously (11,12,18,19,27,33,34). Briefly, the heart and lungs were carefully removed from mice and placed in ice-cold physiological saline solution (PSS) containing (in mM): 130 NaCl, 1 MgSO4, 1.8 CaCl2, 5.4 KCl, 10 HEPES [4-(2-hydroxyethyl)-1-piperazineethanesulfonic acid], and 10 glucose (pH 7.4).…”
Section: Methodsmentioning
confidence: 99%